KECANDUAN KUASA: TIPOLOGI DAN PENYEBAB - Damsar -; Indrayani - (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
This paper discuss on addict of the power, namely people who experienced an addict to the power both legislative and executive arena.  This study try to find answers what kinds of social construction and how to interpret on the power due to people experienced an addict to the power as well as to construct typology of addict of the power. Data on addict of the power were collected through field research on 23 people who were legislative and executive arena in West Sumatra